Development and Evaluation of a LightWeight Electronic Device for the Sampling of Volatile Organic Compounds in the Vertical Coupled to a Captive Metorological Globe (2018)
An understanding of the vertical profile of the composition of volatile organic compounds (VOCs) in polluted urban areas can help to better understand the impact of these compounds on air quality and in the development of better control strategies. To facilitate these types of measurements and they have the necessary reliability, a programmable, lightweight and lowcost VOCs miniaturized sampling device was designed and integrated, that allows to anchor several of them at different heights in the string of a captive instrumented meteorological balloon and also a start/stop control of the samplers that can be operated from the ground. Simultaneous sampling ensures that the vertical profile of the captured VOCs, represents with better certainty the expected differences in the concentration of these compounds due to the influence of the urban canopy layer and urban activity. Each sampling device consists of an electronic circuit that receives the start or stop signal of the air suction mini-pump from a master control system that is on the surface and that allows radio frequency operation. The capture of VOCs is carried out by packed cartridges with an appropriated adsorbent medium for this purpose. The feasibility of the miniaturized system was demonstrated in a short sampling campaign at the levels 0 m, 50 m, and 100 m above ground at a site southwest of the Metropolitan Area of Mexico City during April 2017. The profiles of the determined VOCs concentrations were compared with previous records obtained at the surface level and in vertical profiles using less dynamic sampling methods, demonstrating the benefit of knowing the concentration at different heights in the interpretation of atmospheric chemistry associated with these profiles.